Multifunctional Landscapes that reconcile food production, with ecosystem restoration and biodiversity conservation - Edward-Uwadiale, Regina (CGIAR System Organization, 2025)
This blog, the first in the “Thriving Landscapes, Vibrant Futures” series, outlines the vision and work of the CGIAR Multifunctional Landscapes Science Program, which aims to foster landscapes that are biodiverse, low-emission, and productive while supporting ecosystem restoration and human well-being. It highlights innovations co-designed with local partners—such as community seed banks that conserve and exchange diverse crop and tree varieties, agroecological soil regeneration practices, and holistic land-management approaches like aggregated farms. The piece also describes tools like the Holistic Localized Agroecology Performance Assessment (HOLPA) for evaluating agroecological transitions and participatory rangeland management efforts. Through integrated solutions across Africa, Asia, and Latin America, the program demonstrates how diverse, locally adapted practices can strengthen resilience, nutrition, livelihoods, and conservation outcomes in multifunctional landscapes.